Board Characteristics and the Firm Performance: Evidence from China Public Listed Companies - Li, Mengya (2020)
This paper investigates the relation between the characteristic of the board and the firm performance. It could be highlighted the important role of the board in improving the company performance. The main five features of the board are to be selected as independent variables, such as the size of the board, the independence of the board, board meeting, duality and the establishment of the audit committee. Return on assets (ROA) is to be taken as a proxy to evaluate the performance of the company. The study adopts panel data techniques to measure the influence of board characteristic on financial performance. By using the sample of 111 China-listed firms in the real estate industry for the period of 2017 to 2019, the finding of the study illustrates that the frequency of board meeting and the establishment of audit committee represent a statistically significant effort on corporate performance. Unlike the results of previous empirical researches made concerning this topic, this study fails to find the significant relationship between the size of the board, board independence and duality with corporate performance. In the end, the results of the study may give some suggestions for future study in terms of the corporate governance’ effectiveness to corporate performance. Key words: board of directors, corporate governance, corporate performance